Pancasila as Extraction of Sacred Conscript and Social’s Exegesis in Indonesia’s Diversity - Siregar, Muhammad Habibi (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2022)
This article discusses another dimension in the discussion about Pancasila, which aims to create a conducive climate in establishing a social order in society. Many Muslim scholars see Pancasila as the best interpretation, which aligns with the values of the holy book in Islam. Pancasila has a significant role in maintaining the integrity of the Indonesian state and opposing disintegration. In a fragile situation, the pressure to maintain unity is increasing, and Pancasila is the only option to connect all faiths in a society as diverse as Indonesia. This article shows that, as Indonesia's basic interpretation according to Islamic normative texts, Pancasila is the most reliable concept in formulating equality of belief and justice before the law for all people. The research findings show Pancasila's significant contribution to maintaining Indonesia's integrity by ensuring that all elements can contribute to achieving the best results, not only in the field of religion but also in building national pride. Thus Pancasila plays an essential role in maintaining the unity and integrity of the Indonesian state. Pancasila creates a conducive social climate and conforms to Islamic values.